Interdisciplinary Approach to a Tooth with Open Apex and Persistent Sinus - Anoop N. Das; Krishnamohan Geetha; Ajay Varghese Kurian; Radhakrishnan Nair; K. Nandakumar (Hindawi Limited, 2015)
Traumatic injuries in childhood may disrupt root development leading to a tooth with open apex. Apexification procedures in such cases aim at root end closure after reasonable period of time. In some chronic cases, complete healing of the periapical area does not occur resulting in development of a nonhealing sinus. Failure of nonsurgical approach in such cases needs surgical intervention permitting thorough periapical curettage. In the present case, apexification procedure with MTA achieved root end closure but failed to heal the sinus for which surgical treatment was completed with thorough periapical curettage and application of platelet rich fibrin (PRF) and a combination of β-tricalcium phosphate and hydroxyapatite resulted in healing.